Balance of paymentsconstrained growth models: History and overview - A. P. Thirlwall (University of Kent, School of Economics, 2011)
This paper surveys balance of payments constrained growth models from Thirlwall's original contribution in 1979 to the latest tests of the model using cointegration techniques. Historical antecedents of the model are explored (e.g. the Harrod trade multiplier; dual gap analysis; Prebisch's centre-periphery model), and various extensions of the model are outlined including: capital flows; interest payments on debt, and generalisation of the model to include many countries and many goods. All the empirical literature, using time series, panel and cross section data, is documented with discussion of the tests employed. The basic model that long run GDP growth can be approximated by the ratio of export growth to the income elasticity of demand for imports is remarkably robust. The relevance of the model is shown for the current discussion of global imbalances in the world economy.
Keywords: F02; F32; F43; 330; balance of payments constrained growth; Harrod trade multiplier; north-south models; global imbalances